ANALISIS POSTUR KERJA PADA SUPIR TRUK PT. ZAFANA MAS SAKTI MENGGUNAKAN METODE RULA DAN REBA - Zarkasyi, Muhamad Hikam Fauzi; Hanan, Siti; Rini, Asih Setyo; Kustandi, Ogie; Doto, Doto (LPPM Universitas Bina Bangsa, 2023)
Observation using Nordic Body Map to truck drivers, complaints that are often felt include: the upper and lower parts of the neck, waist, buttocks, and left leg due to less ergonomic driving positions such as the driver's seat that is less high, the left leg often hurts due to frequent stepping on the clutch and long enough sitting time in a static position resulting in complaints of Musculoscletal Disosders (MSDs). To reduce the risk of injury to the driver, research was conducted using the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) methods by looking at the results of the score value. The RULA score of respondent 1 is 5 medium risk levels, respondent 2 is 5 medium risk levels, respondent 3 is 4 small risk levels. While the results of respondent 1's REBA score are 6 medium risk levels, respondent 2 is 6 medium risk levels, respondent 3 is 4 medium risk levels. The improvements made are adjusting the car seat so that the steering wheel position is parallel to the forearm, elevating the car seat so that the driver's head position can be parallel to the car glass